2013
DOI: 10.1080/00223980.2013.781498
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Copenhagen Burnout Inventory—Chinese Version

Abstract: The Copenhagen Burnout Inventory is a measurement scale that assesses the degree of burnout in the personal, work, and client domains. The aim of this study was to examine the psychometric properties of the inventory's Chinese version (CBI-C) in a sample of 312 human service workers in Hong Kong with follow-up assessment for 245 participants. The results of confirmatory factor analyses show the revised three-factor model to have an adequate fit in the baseline and cross-validation samples. The CBI-C demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 25 publications
19
48
1
Order By: Relevance
“…7,8 Our results from reliability analyses showed that CBI (both its 3-factor and global factor structures) presented good internal consistency. These results are aligned with other studies from different populations, such as Taiwan employees, 9 Chinese Human Service workers, 27 and Australian dentists. 28 Results from the average variance extracted showed that the three subscales presented good discriminant validity, except between the personal and workrelated subscales.…”
Section: Discussionsupporting
confidence: 90%
“…7,8 Our results from reliability analyses showed that CBI (both its 3-factor and global factor structures) presented good internal consistency. These results are aligned with other studies from different populations, such as Taiwan employees, 9 Chinese Human Service workers, 27 and Australian dentists. 28 Results from the average variance extracted showed that the three subscales presented good discriminant validity, except between the personal and workrelated subscales.…”
Section: Discussionsupporting
confidence: 90%
“…[4] The results of the test-retest revealed that the Persian version of the instrument has a good stability, which confirms the findings reported by Fong et al . [34] about the Chinese version of CBI.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Work burnout Copenhagen Burnout Inventory-Chinese Version (Fong et al, 2014) 19-item self-report scale with 3 sub-scales: personal burnout, work-related burnout, and client-related burnout…”
Section: Ordinal and Nominalmentioning
confidence: 99%